Significant organizational problems faced by Sarawak economic development corporation / Jamil Hj. Jamaludin - Hj. Jamaludin, Jamil (Faculty of Accountancy, 1986)
The research seeks to study the significant problems faced by an organization from the point of view of the Director, Personnel Officer and the Accountant, as part of the requirement of Organization Behaviour subject for this semester. Information were gathered from various resources such as Bibliographical research, interviews, questionnaires and secondary data-internal source. The beginning part deals with the introduction which explained, the objectives and purposes as well as a brief description regarding the scope of the research. Then after completing another aspect that is the limitation to the scope of research will be Chapter I on the methodology and approach of the research that have been used to provide and collect information for the purpose of this particular research. A Chapter 2 deals with the review from related literature concerning the definitions as well as various other relevant materials essential to meet the requirement of the research. Chapter 3 will be the highlight of the research that is the significant problem faced by Sarawak Economic Development Corporation, their causes as well as the ways and means to overcome the problems. Following these will be the recommendation which will be based on the corrective measure taken by the management of the Corporation for the respective problems. In concluding the research, emphasis will be done on the overall conclusion and recommendation pertaining to the problems by relating the findings and analysis to the objectives.